Crystalline structure and morphology in uniaxially oriented polypropylene film modified with nanosilica. Issue 11 (29th July 2019) - Liu, Hui; Li, DongLi; Xu, Wencai; Fu, Yabo; Liao, Ruijuan; Shi, Jiazi; Wang, Yajun
Abstract : Silica‐polypropylene (PP) composite resins were prepared with nanosilica particles and PP resin through melt blending. This composite resin was used to prepare uniaxially oriented PP film under certain conditions. Surface and cross‐section morphologies of the PP films were analyzed by SEM, while the crystalline phase, crystalline orientation, and grain size of the PP films were analyzed by X‐ray diffraction (XRD). Crystallinity was analyzed by differential scanning calorimetry (DSC). The mechanical properties, heat resistance, and barrier properties of the film were tested and analyzed. The PP melts formed shish‐kebab structure when subjected to shearing or stretching at near‐melting temperatures. The ratio of the intensity of the XRD of 040 crystal surface to that of the 110 crystal surface was greater than 0.71. The modified polypropylene melt was subjected to tensile action at 30°C on a cooling roller, resulting in a specially oriented structure. However, the ratio of the intensity of the XRD of the 040 crystal surface to that of the 110 crystal surface did not change. Under the same processing conditions (ie, low cooling temperature and high unidirectional tension), a transverse 040 wafer was formed on the surface of the unmodified film, but polypropylene film modified by nanosilica was not found. The fiber‐like shish‐kebab structure with regular arrangement appeared on the film. The change in the microstructure of the modified polypropylene film resulted in a material with excellent mechanical properties, toughness, barrier property, and heat resistance. Abstract : Silica‐polypropylene (PP) composite resins were prepared with nanosilica particles and PP resin through melt blending. This composite resin was used to prepare uniaxially oriented PP film under certain conditions. The fiber‐like shish‐kebab structure with regular arrangement appeared on the film. The change in the microstructure of the modified polypropylene film resulted in a material with excellent mechanical properties, toughness, barrier property, and heat resistance.